The Lankes Corollaries - Lankes, R. David (Access: An International Journal of Nepal Library Association, 2023)
This piece explores a series of corollaries to Ranganathan’s five laws of librarianship. These corollaries talk about how librarians work with community’s to ensure that service is shaped throughout the community. Such shaping moves libraries away from some pre-determined standard model, and into hyper local organizations ultimately facilitating knowledge creation.